Modeling Alzheimer’s disease using human cell derived brain organoids and 3D models - Fernandes, Sarah; Revanna, Jasmin; Pratt, Joshua; Hayes, Nicholas; Marchetto, Maria C.; Gage, Fred H. (Frontiers in Neuroscience, 2024)
Age-related neurodegenerative diseases, like Alzheimer's disease (AD), are challenging diseases for those affected with no cure and limited treatment options. Functional, human derived brain tissues that represent the diverse genetic background and cellular subtypes contributing to sporadic AD (sAD) are limited. Human stem cell derived brain organoids recapitulate some features of human brain cytoarchitecture and AD-like pathology, providing a tool for illuminating the relationship between AD pathology and neural cell dysregulation leading to cognitive decline. In this review, we explore current strategies for implementing brain organoids in the study of AD as well as the challenges associated with investigating age-related brain diseases using organoid models.